THE IMPACT OF RISK FACTORS ON ORAL HEALTH - Ulug‘bekova Dildora Ravshanbek qizi (Web of Journals Publishing, 2025)
The oral cavity is an important part of the human body. It is involved not only in the process of receiving and digesting food, but also in breathing, speech and many other functions. Also, the oral cavity can be a gateway for various diseases and pathologies. Risk factors, which are harmful to health, can negatively affect the oral cavity. This article details the impact of risk factors on the oral cavity, their causes and preventive measures.
Keywords: Oral cavity, diseases, pathology, eating habits, digestive process, gingivitis and periodonti.